DEVELOPING AESTHETIC PERCEPTION AND CREATIVE APPROACHES IN FINE ARTS EDUCATION AT HIGHER INSTITUTIONS (Web of Teachers: Inderscience Research, 2025)
This article examines methods for developing aesthetic perception and fostering creative approaches in fine arts education at higher institutions. The study focuses on pedagogical strategies that combine observational analysis, project-based tasks, and multimedia tools to enhance students’ artistic literacy, critical thinking, and creative problem-solving skills. Emphasis is placed on practical techniques to engage students actively, promote independent exploration, and cultivate reflective learning in the visual arts.